How appropriate is the balanced scorecard as an internal reporting framework? / Paul Mountcastle and Noel Yahanpath - Mountcastle, Paul; Yahanpath, Noel (Penerbit UiTM (UiTM Press), 2015)
The Balanced Scorecard (BSC) remains a popular strategic management tool. This tool has also been successfully applied in the healthcare industry aside from various business fields. However, the use of BSC in New Zealand lacks evidence, thus requiring further research into the applicability of this tool in the country, especially when the Hawke's Bay District Health Board (HB DHB) sought to improve its internal reporting framework. In this case, we investigated whether BSC could be applied by HB DHB in pursuing its objective. Given the lack of an international standard for healthcare BSC design, we developed a framework that comprised the appropriate perspectives to meet the needs and internal reporting requirements of HB DHB. BSC was eventually proven suitable for this application, and the framework of Marr (2015) was identified as a suitable framework for such an application. While remaining to the original design of Kaplan and Norton, the framework has been modified to fit the needs of HB DHB by changing the customer perspective to community and by adopting Marr's positioning of the financial perspective along with three other perspectives to reflect the importance of both financial constraints and objectives to the whole operation.